Vibrations of a Complex Systems with Damping under Dynamic Loading - Cabanska-Placzkiewicz, K. (Проблемы прочности, 2002)
This paper introduces an analytical-numerical method for solving a problem related to free and forced damping vibrations of a sandwich system that consists of two plates coupled with a viscoelastic interlayer. On the basis of the designed method we perform numerical analysis by means of the Timoshenko and the Kirchhoff-Love models and investigate new mechanical effects attributable to the action of various types of dynamic loading on the system considered.